IMPLEMENTASI MODEL PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 08 MERANGIN - Napisya, Mutiara; Yusria; Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of differentiated instruction in Islamic Religious Education (PAI) to enhance students’ learning motivation at State Junior High School 08 Merangin. Although differentiated learning has been introduced in line with the Merdeka Curriculum to accommodate students’ readiness, interests, and learning profiles, its implementation in practice has not shown optimal results in improving students’ motivation. This research employed a qualitative descriptive approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving PAI teachers, school principals, and students as research subjects. The findings revealed that the implementation of differentiated instruction had been carried out through adjustments in content, process, and product; however, it was not yet fully optimal due to several inhibiting factors, including limited teacher understanding, time constraints, inadequate learning facilities, and insufficient institutional support. These obstacles contributed to low student engagement, lack of enthusiasm, and minimal participation during learning activities. The study concludes that effective implementation of differentiated instruction requires continuous professional development, collaborative support, adequate resources, and systematic evaluation to ensure that the model can significantly enhance students’ intrinsic learning motivation in Islamic Religious Education.